(untitled) (Foro de Educacion, 2023)
Until 1973 Higher Education in Chile was free for the 8 existing universities -2 publics and 6 privates-. The military dictatorship began to reduce the state’s contribution of funding through the implementation of a market policy in education; from 1981 on a larger decline begins and private universities are enabled to be created; to this end, it issues three decrees amending the composition of higher education. This situation was maintainedwith the return to democracy in 1990 and scholarships and financial support were established with a return. Starting in 2016, the gratuitousness’s policy began again, initially for 50% of students from lower-income families; it was then increased to 60% and will gradually increase in time by increasing the percentage to reach 100%. It is pursued, on the basis of the relevant legislation, to analyze the period under study with a historical-analytical methodology.